Transferability of the EST-SSRs developed on Nules clementine (Citrus clementina Hort ex Tan) to other Citrus species and their effectiveness for genetic mapping - Luro, Francois; Constantino, Gilles; Terol, Javier; Argout, Xavier; Allario, Thierry; Wincker, Patrick; Talón, Manuel; Ollitrault, Patrick; Morillon, Raphael (Springer Nature, 2020)
Abstract Background During the last decade, numerous microsatellite markers were developed for genotyping and to identify closely related plant genotypes. In citrus, previously developed microsatellite markers were arisen from genomic libraries and more often located in non coding DNA sequences. To optimize the use of these EST-SSRs as genetic markers in genome mapping programs and citrus systematic analysis, we have investigated their polymorphism related to the type (di or trinucleotide) or their position in the coding sequences.